2022
DOI: 10.1039/d2se01259f
|View full text |Cite|
|
Sign up to set email alerts
|

Manipulation of oxygen evolution reaction kinetics of a free-standing CoSe2–NiSe2heterostructured electrode by interfacial engineering

Abstract: Electrodeposition is a facile and scalable strategy to prepare free-standing OER electrodes with promising electrocatalytic activity, high active site utilization, and fast mass transportation. In this study, hierarchical CoSe2-NiSe2 heterostructured...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Rauf and co-workers synthesized layered CoSe 2 /NiSe 2 compounds for OER, which showed the overpotential of 310 mV at 10 mA cm −2 in 1 m KOH. [222] Qi and co-workers prepared a series of CoTe 2 /NiTe 2 /CoNi composites via a facile method, the optimized CoTe 2 /NiTe 2 /CoNi composites showed a low Tafel slope (19.4 mV dec −1 ) and a low overpotential (280 mV@10 mA cm −2 ) for OER in 1 m KOH. [219] In this part, the different types of LMCs-based composites for OER have been summarized, and these studies have confirmed that such LMCs-based composites are excellent materials for electrocatalytic oxygen evolution.…”
Section: Oxygen Evolution Reactionmentioning
confidence: 99%
“…Rauf and co-workers synthesized layered CoSe 2 /NiSe 2 compounds for OER, which showed the overpotential of 310 mV at 10 mA cm −2 in 1 m KOH. [222] Qi and co-workers prepared a series of CoTe 2 /NiTe 2 /CoNi composites via a facile method, the optimized CoTe 2 /NiTe 2 /CoNi composites showed a low Tafel slope (19.4 mV dec −1 ) and a low overpotential (280 mV@10 mA cm −2 ) for OER in 1 m KOH. [219] In this part, the different types of LMCs-based composites for OER have been summarized, and these studies have confirmed that such LMCs-based composites are excellent materials for electrocatalytic oxygen evolution.…”
Section: Oxygen Evolution Reactionmentioning
confidence: 99%